Opioid prescription patterns in the province of Las Palmas, Canary Islands, Spain (2016–2020): differences between urban and rural areas - Oliva, Alexis; González de Chavez, Patricia; Dévora, Sandra; Abdala, Susana (Frontiers in Pharmacology, 2023)
The use of opioids has increased markedly in the past decades in European countries, especially for treatment of non-cancer pain including painful chronic musculoskeletal conditions. However, there are some notable differences in the relative levels of use between geographical areas and some distinct, context-specific patterns of weak and strong opioid use. The aim of this work is to describe real world trends in dosage forms and population exposure in the prescription opioid use on isolated geographically area: The Canary Islands of Gran Canaria, Lanzarote and Fuerteventura, Spain. For this, several factors such as living in a rural or urban area, population over sixty-five years of age, population density or socioeconomic status were analyzed. Data were extracted from the wholesalers who supply the community pharmacies at the population level. Prescription opioid use was measured as defined daily doses (DDD) per 1,000 inhabitants per day. A model based on covariance analysis with two nested fixed factors and one covariable was used for contrast analysis at different level.The overall DDD per 1000 inhabitants per day and year variation rate in Spain was very similar to that obtained for Gran Canaria and Fuerteventura (0.967 vs 1.006), although the levels of dispensation were different (14.75 versus 18.24 for Gran Canaria and 12.7 for Fuerteventura, respectively). Lanzarote is completely different in all issues, where the opioid consumption rate remained stable during the study period, but with a decreasing tendency. The dispensation level of strong opioids varied between islands, from 56.41% for Fuerteventura vs 17.61% for Gran Canaria, although these values remained stable.Tramadol with acetaminophen and Tramadol in monotherapy were the most consumed forms of the weak opioids, whereas Buprenorphine was the most used strong opioid followed by Fentanyl, although demand for it varied between islands, the transdermal formulations were the most frequent pharmaceutical preparation.The differences in prescription opioid use are most likely explained by the opioid prescribing practices in each island, whereas factors such urbanicity level, population age, population density and status socioeconomic does not help to explain the differences in prescription opioid use across rural and urban areas.